Association of hyperuricemia with dietary patterns and alcohol consumption in the adult population. Results of the ESSE-RF epidemiological study - N. S. Karamnova; O. B. Shvabskaya; A. I. Rytova; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; M. B. Kotova; S. A. Maksimov; G. A. Muromtseva; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To study the associations of hyperuricemia (HU) with dietary patterns and alcohol consumption in the Russian population.Material and methods. Representative samples of male and female population aged 25-64 years (17929 people, including 6593 men and 11336 women) from 13 Russian regions were examined. The response rate was ~80%. The dietary pattern was studied by the consumption rate of the main food groups. HU was diagnosed at a uric acid (UA) level >400 μmol/l for men and >360 μmol/l for women. The results are presented as odds ratio (OR) and 95% confidence interval (CI).Results. People with HU more often consume fish (men by 28% and women by 34%) (p<0,005), less often — sweets (by 22 and 21%, respectively) (p<0,001) and cheese (by 13 and 14%, respectively) (p<0,05). In the diet of individuals with HU, excess sugar consumption is lower by 19 and 23% in men and women, respectively (p<0,001). Women with HU also have 13% lower red meat consumption, 36% lower legume consumption, 28% higher poultry consumption (p<0,001) and 25% lower low-fat dairy products (p<0,05), as well as 15% lower animal fat use in cooking (p=0,008) compared to individuals without HU. Individuals with HU do not discontinue alcohol, but its consumption is lower than in individuals without HU. In men, the amount of alcohol consumed has a linear association with the UA level of and HU risk. In general, among male alcohol consumers, the risk of HU is 1,32 [1,13-1,54] (p=0,001). In men with low alcohol consumption, the risk of HU is 1,24 [1,05-1,45] (p=0,009), with moderate and high consumption — 1,61 [1,32-1,97] (p<0,001) and 1,64 [1,27-2,12] (p<0,001), respectively.Conclusion. The diet of individuals with HU differs significantly from the diet of individuals without HU, which is more pronounced among women. In men, the risk of HU increases linearly with the amount of alcohol consumed.